2019
DOI: 10.1002/smll.201903896
|View full text |Cite
|
Sign up to set email alerts
|

Growth of Single‐Walled Carbon Nanotubes with Different Chirality on Same Solid Cobalt Catalysts at Low Temperature

Abstract: Single-walled carbon nanotubes (SWNTs), since reported in 1993, [1] have been regarded as a promising material owing to unique structure-dependent properties, especially in nanoelectronics applications. [2,3] Therefore, tremendous efforts have been made to pursue the specific-chirality growth of SWNTs, including designing various catalysts [4][5][6][7][8][9] and growth process con-trolling. [10][11][12] Despite of some progresses made in chirality selective synthesis of SWNTs, the mechanism for the experiment … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
18
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
6
1
1

Relationship

2
6

Authors

Journals

citations
Cited by 15 publications
(18 citation statements)
references
References 25 publications
(27 reference statements)
0
18
0
Order By: Relevance
“…However, to utilize their template effects during the CVD process, a low reaction temperature is required to preserve the solid state. For example, Zhang et al reported a rational approach to grow horizontally aligned SWNTs with different chiralities on Co catalysts at a temperature of 650 °C, 233 as schematically illustrated in Figure 41a. On the Co(111) facet, armchair SWNTs possess the most stable edge structure because of the tight SWNT−catalyst contact.…”
Section: Electronic Property Control In the Synthesis Of Horizontally...mentioning
confidence: 99%
See 1 more Smart Citation
“…However, to utilize their template effects during the CVD process, a low reaction temperature is required to preserve the solid state. For example, Zhang et al reported a rational approach to grow horizontally aligned SWNTs with different chiralities on Co catalysts at a temperature of 650 °C, 233 as schematically illustrated in Figure 41a. On the Co(111) facet, armchair SWNTs possess the most stable edge structure because of the tight SWNT−catalyst contact.…”
Section: Electronic Property Control In the Synthesis Of Horizontally...mentioning
confidence: 99%
“…Raman spectra of SWNTs grown using (b) thermodynamic control and (c) kinetic control. Reproduced with permission from ref . Copyright 2019 John Wiley and Sons.…”
Section: Chemical Vapor Deposition Synthesis Of Horizontally Aligned ...mentioning
confidence: 99%
“…Zhang et al reported chirality-controlled growth of SWCNTs by keeping the Co catalyst in solid state using lower temperature (650°C) [171]. Their method is based on the symmetry matching mechanism [172], where Co (100) face is used as template to grow horizontal arrays of near-armchair tubes (10,9) with 75% selectivity and (12, 6) with 82% selectivity.…”
Section: Low Temperature Growth Of Swcntsmentioning
confidence: 99%
“…The catalyst was spin coated on quartz substrate using Co(NO 3 ) 2 ethanol solution. In order to achieve (10,9) tubes requiring slower growth rate, they used minimum concentration of ethanol to tune the thermodynamic selectivity, whereas for (12, 6) tubes requiring higher growth rate, they used CO to provide higher concentration of carbon while etching away the excessive amorphous carbon by oxygen radicals to maintain the catalytic activity [171].…”
Section: Low Temperature Growth Of Swcntsmentioning
confidence: 99%
“…Because these methods were not easy to implement as a routine evaluation of a large number of samples, many research groups have shifted towards using variations of the same micro-Raman mapping-based alternative methodology. This methodology relies on accumulating spectra at the nodes of a grid over the surface of the sample in a Raman microscopy setup using several discrete laser lines, and counting RBM peaks as individual SWCNTs regardless of their intensity [17,18,19,20,21,22,23,24,25,26,27]. We will refer to this as the Raman peak counting, or RBM peak counting methodology.…”
Section: Introductionmentioning
confidence: 99%